2021
DOI: 10.3138/cpp.2020-157
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Energy Impacts of Telework in Canada

Abstract: Quantifying the energy impact of teleworking has been challenging due to the low prevalence of telework. The COVID-19 pandemic and the associated widespread shift to telework provides a new opportunity to study the energy impact of teleworking. Within two months of the lockdowns we surveyed 278 knowledge-based workers in Canada who started primarily working from home to investigate their energy-related behaviours and attitudes. The survey’s major themes are energy-saving actions taken in the office, equipment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Findings from one recent study attempting to learn lessons from the pandemic reveal that there is not likely to be any reduction in emissions overall and the net result may be a small increase (Santos and Azhari, 2022). A recent Canadian study suggested that if workers continued to operate from home and maintained their existing energy consumption arrangements--or even close to those levels--this could lead to an escalation in energy consumption and amplified peak loads, and it would be challenging and financially costly for electricity suppliers to exactly match various supply and demand loads during the day (Villeneuve et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from one recent study attempting to learn lessons from the pandemic reveal that there is not likely to be any reduction in emissions overall and the net result may be a small increase (Santos and Azhari, 2022). A recent Canadian study suggested that if workers continued to operate from home and maintained their existing energy consumption arrangements--or even close to those levels--this could lead to an escalation in energy consumption and amplified peak loads, and it would be challenging and financially costly for electricity suppliers to exactly match various supply and demand loads during the day (Villeneuve et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As Guarin et al [75] pointed out, the energy demand saved by reduced commuting may be overestimated if it is not corrected by the increase in residential energy demand. Furthermore, as discovered in the study by Villeneuve et al [68], the induction and time rebound effects of working from home can significantly impact residential energy demand. In their study, telecommuters increased their indoor temperature to increase their comfort while working from home.…”
Section: Exploiting the Synergies Between Ict Applications And Differ...mentioning
confidence: 96%
“…Surveys' results [61][62][63][64][65][66][67] indicated that teleworking allows households to reduce the number of trips and miles traveled compared to those who do not perform teleworking (changed practice effect). Additionally, time saved due to a reduction in commuting can be reused by households (time rebound effect) to perform other activities (working, leisure time, shopping, and household tasks) [61,68]. Increasing the time spent at home can induce additional behavioral change, such as increasing the apartment's indoor temperature [68].…”
Section: The Case Of Teleworkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the pandemic started, telework has increased precipitously and appears likely to remain higher than before ( Sweet and Scott, 2022 ). Many potential benefits from telework have been touted, including energy savings ( Villeneuve et al, 2021 ), congestion alleviation ( Nguyen, 2021 ) and real estate cost savings ( Ruth and Chaudhry, 2008 ). But longer-term impacts on cities are also possible, including urban spatial restructuring, local fiscal pressure, inter-jurisdictional fiscal competition and weaker unions ( Brueckner et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%